Reimagining Education Financing in Nepal: A Policy and Budget Analysis - Khatiwada, Shreeraj (Journal of Emerging Management Studies, 2025)
Purpose - Education in Nepal is constitutionally guaranteed as a fundamental right and is viewed as central to social transformation and human capital development. This study aims to examine how the Ministry of Education, Science and Technology’s (MoEST) budget allocations from FY 2021/22 to FY 2025/26 address the interconnected goals of equity, quality, employability, and governance in education.Design/methodology/approach - The research employs the Alignment of Resources, Policies, and Outcomes (ARPO) framework, integrating national budget data with policy documents and comparative insights from UNESCO, the World Bank, and the Asian Development Bank. A qualitative policy and budget analysis approach was used, combining fiscal trend analysis with thematic interpretation to assess coherence and alignment with both national objectives and international benchmarks.Findings and Conclusion - The findings reveal steady growth in MoEST’s budget, with significant emphasis on equity-focused interventions such as scholarships, mid-day meals, and free textbooks. However, persistent challenges remain in quality improvement, governance, and labor-market alignment, as reflected in the declining performance of government schools and widening disparities between public and private education. The study concludes that meaningful reform requires systemic improvements in curriculum design, leadership development, accountability, and vocational training, alongside stronger industry-education collaboration.Implications - The analysis highlights that fiscal investment alone cannot transform Nepal’s education sector. Effective reforms can strengthen governance, enhance school leadership, expand vocational pathways, and integrate technology to bridge access and quality gaps. Lessons from international best practices suggest the need for inclusive governance, teacher collaboration, digital readiness, and curriculum contextualization to build a future-ready education system.Originality/value - This study offers one of the first longitudinal analyses of MoEST’s budget allocations post-pandemic within the federal governance structure, applying the ARPO framework to connect fiscal trends with social outcomes. It contributes to the literature by situating Nepal’s education financing within global debates on equity, quality, and human capital development, while proposing contextually rooted reforms for sustainable transformation.